Indonesian English Learners’ Perception of The Implementation of Mobile Assisted Language Learning in English Class - Ahmad Lizamuddin; Abdul Asib; Ngadiso Ngadiso (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2019)
Many Indonesian English Learners nowadays use the smartphone as their communication tools. It is used only for socializing through social media by most of them. This descriptive research aims to elaborate their perception on the implementation of MALL in English Class for University Level. The data were collected through a survey questionnaire which was adapted from the Technology Acceptance Model (TAM). The result proves that they have a positive perception on the usage of MALL.